1997
DOI: 10.1071/aj96009
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Potential of Glacio-Fluvial Sandstones: Merrimelia Formation, Cooper Basin, South Australia

Abstract: Sedimentological analysis of cored sections within the Merrimelia Formation (basal Gidgealpa Group, Cooper Basin, S.A.) reveals a complex glacigenic environment, including glacio-lacustrine, deltaic, shorezone, fluvial, aeolian and other terrestrial facies. These facies are observed within terminoglacial and proglacial environments, and interfinger constantly throughout the Merrimelia Formation, exhibiting rapid environment change related to position of the ice sheet. Detailed sedimentological and petrological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…14). Williams and Wild (1984) and Chaney et al (1997) have interpreted this field to be a braided river system, which formed from glaciofluvial braided outwash deposits. Despite reasonably good porosities (around 10%), the Tirrawarra Field has low permeabilities of around 1 mD, which has required secondary recovery methods to sustain production (Skilbeck et al, 1991;Gravestock et al, 1998).…”
Section: Implications For Reservoir Modellingmentioning
confidence: 97%
“…14). Williams and Wild (1984) and Chaney et al (1997) have interpreted this field to be a braided river system, which formed from glaciofluvial braided outwash deposits. Despite reasonably good porosities (around 10%), the Tirrawarra Field has low permeabilities of around 1 mD, which has required secondary recovery methods to sustain production (Skilbeck et al, 1991;Gravestock et al, 1998).…”
Section: Implications For Reservoir Modellingmentioning
confidence: 97%
“…Tillite was formed in topographic lows possibly by moraines in proximity to moving ice sheets, whereas the 'rainout' diamictite was deposited by rafted icebergs. Chaney et al (1997) interpreted the 'rainout' diamictite as high energy glacial melt water deposit accumulated in close proximity to ice sheets in the Australian coal basins. Evenson et al (1977) suggested that the glacial melt water currents ripped up the earlier formed beds and transported down slope as coherent blocks along with ice rafted debris to deposit as intraformational clasts in diamictite similar to those shown in Fig.…”
Section: Coal Forming Environmentsmentioning
confidence: 98%
“…The 'rain out' diamictites were described from the late Carboniferous Gondwana basins of Australia (Chaney et al, 1997) and South Africa (Visser, 1997). Diamictite contains basement derived rocks as extra formational angular clasts, as well as intraformational reworked sandstone and rhythmite fragments (Fig.…”
Section: Vuzi Assemblagementioning
confidence: 99%
“…Map of study area, star symbols showing cored wells and blue dots showing well locations in the Cooper Basin, Australia (modified afterChaney et al, 1997).…”
mentioning
confidence: 99%